Implementation Techniques for Improving Data Quality for Knowledge Discovery in Databases - Sharma, Sarika; Shaikh, Rizwan; Tyagt, Vipin (Gyan Management Journal, 2008)
The companies in today's fast changing competitive world are compiling databases on individual customer o that they can under tand their customers better. The trategy today is to maintain, monitor and analyze cu tomer records not just for adding values but also to have a competitive edge. These records are maintained in lhe form of a cu tamer da abase also known as a data warehou e. Organizational databas are pervaded with th poor quality of data as mo t of the times the data is not collected for the purpose of data mining in the mind, and the sources, which seems to be quite r liable can provide d ilecting information. 1 he data mining tools wh n applied on this efC ctive data will result in poor quality model following the garbage in garbage out for the data.
Keywords: Implementation; Data Quality; Knowledge Discovery; Databases